Laparoscopic Shunt Revision Avoids Many Complications of Open Shunt Revision and Has Outcomes Similar to First-time Shunt Placement. Issue 3 (March 2015) - Logghe, Heather; Maa, John; McDermott, Michael; Oh, Michael; Carter, Jonathan
Open revision of abdominal shunts is associated with increased risk of wound infection, visceral injury, hernia, and shunt complications. We hypothesized that laparoscopic revision mitigates these risks to a level similar to initial (i.e., first-time) shunt placement. This was a single-center, multisurgeon, retrospective cohort study of patients who underwent either laparoscopic initial shunt placement or laparoscopic shunt revision over a 5-year period. Outcomes were operative time, length of stay, and 30-day complication rate. Sixty-nine patients underwent laparoscopic shunt revision and 99 patients underwent laparoscopic initial shunt placement. Operative times were nearly identical (75 vs 73 minutes, P = 0.63). There were no significant differences in blood loss or hospital length of stay. Abdominal complications and total complications did not differ between groups. Laparoscopic shunt revision avoided many of the known complications of open shunt revision and had outcomes similar to initial laparoscopic shunt placement.